Genetic variability and divergence studies to identify and isolate superior genotypes from European radish (Raphanus sativus) germplasm - MADAIK, SPARSH; BHARDWAJ, RAMESH K; VIKRAM, AMIT; DOGRA, R K; THALYARI, JEENIA (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried during the winter (rabi) seasons of 2019–20 and 2020–21 at Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to identify and isolate superior genotypes from European radish (Raphanus sativus L.) germplasm. The experiment was laid out in randomized block design (RBD) comprising of 25 genotypes with three replications. These genotypes were evaluated for various horticultural and yield contributing traits, using the popular check cultivar Pusa Himani as a reference. The combined data from two years revealed significant differences among all the genotypes for the studied traits. Notably, genotypes UHF-SOL-RAD-3, UHF-SOL-RAD-1 and RKR-Sel-III exhibited higher yields compared to the check variety and performed well across most traits. The root top ratio demonstrated the highest phenotypic and genotypic coefficient of variability (34.79% and 34.64%, respectively). Traits such as total soluble solids (TSS), average root weight, root yield, gross plant weight, root top ratio (length basis), and root length exhibited moderate to high heritability along with moderate genetic advances. Based on Mahalanobis D2 statistics, five clusters were identified, with a majority of genotypes falling into cluster II. Cluster III displayed the highest intra-cluster similarity (51.18%), while clusters I, III, and V demonstrated greater diversity, thereby increasing the likelihood of obtaining favourable transgressive segregants through hybridization between genotypes in these clusters.